Acceptance and Commitment Therapy: model, data, and extension to the prevention of suicide (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
The present article briefly describes ACT, its underlying model, and the evidence in support of its efficacy. In order to provide an example of how to extend ACT to new problems, the paper then extends ACT thinking to the prevention of suicide and suicidality. ACT, both its model and applied techniques, appears to be supported by the evidence, suggesting that further extensions are warranted.